From maps to models: Key concepts in Geographic Information Systems - Yohannes Shifera Daka; Kassaye Hussein; Ashenafi Yimam (Computational Ecology and Software)
Geographic Information Systems (GIS) have dramatically altered the landscape of spatial data analysis, which have allowed practitioners and scholars to gain important insights in a variety of domains, including emergency response, environmental management, and urban planning. Central to the functionality of GIS are two integral components: maps and models. Although maps have historically been used to graphically and statically depict spatial data, GIS models go beyond static representations to turn maps into dynamic, predictive tools. These models help predict and analyze spatial dynamics across time by simulating real-world phenomena. These models allow for simulations of real-world phenomena, aiding in forecasting and analyzing spatial processes over time. This paper explores the evolution of GIS, focusing on the shift from traditional cartographic maps to dynamic models, highlighting how these advancements have revolutionized spatial analysis and influenced real-world applications. An understanding of how GIS is influencing the future of spatial data interpretation is provided by the exploration of the interaction between maps and models.